British Nuclear Medicine Society Clinical Guideline for bone scintigraphy. Issue 11 (27th September 2022) - Graham, Richard; Little, David; Cade, Sarah; Redman, Stewart
Abstract : This guideline must be read in conjunction with the British Nuclear Medicine Society (BNMS) Generic guidelines. The purpose of this guideline is to assist specialists in Nuclear Medicine and Radionuclide Radiology in recommending, performing, interpreting and reporting the results of bone scintigraphy studies. This guideline could also be used to help individual departments formulate their own local protocols. This does not aim to be prescriptive regarding technical aspects of individual camera acquisitions, which should be developed in conjunction with the local medical physics expert.